Effect of fluoride on PERK-Nrf2 signaling pathway in mouse ameloblasts. (July 2019) - Zhou, X; Chen, Z; Zhong, W; Yu, R; He, L
In the development of dental fluorosis, oxidative stress is considered as the key mechanism. Endoplasmic reticulum (ER) stress can induce oxidative stress and activate the important antioxidative factor nuclear factor erythroid 2-related factor 2 (Nrf2) in a PKR-like ER kinase (PERK)-dependent manner, but combining ER stress and oxidative stress, the role of PERK-Nrf2 signaling pathway involved in fluoride-regulated ameloblasts is not fully defined. Here, we studied the effect of fluoride on PERK-Nrf2 signaling pathway in mouse ameloblasts. We found that low-dose and continuous fluoride exposure increased binding immunoglobulin protein expression and activated PERK–activating transcription factor 4 signaling pathway. Meanwhile, the expression of Nrf2 and its target genes (glutamylcysteine synthetase and glutathione S -transferase-P1) enhanced following ER stress. Tunicamycin increased the expression of PERK, leading to Nrf2 nuclear import, and tauroursodeoxycholate suppressed Nrf2 activation through PERK during ER stress, indicating that PERK activation is required for Nrf2 nuclear entry. Furthermore, tert-butylhydroquinone triggered the overexpression of Nrf2 to reduce ER stress, but luteolin inhibited Nrf2 nuclear localization to elevate ER stress. In summary, this study proved that fluoride under certain dose can induce ER stress and promote Nrf2 nuclear import via PERK activation and suggested that antioxidation mechanism mediated by PERK-Nrf2 can alleviate fluoride-induced ER stress effectively.